Perceived satisfaction with sweetened condensed milk in Malaysia - Ong, Victor Ching Poh *; Sri Sivabalan Danapalam *,; Choy, Tuck Yun * (2012)
Purpose: This research examined factors that would influence customer satisfaction of premium-priced Brand X sweetened condensed milk among teh-tarik restaurant operators in Peninsular Malaysia. Approach: Past literature suggested that factors such as perceived quality, logistic process responsiveness, sale force effectiveness, brand association and trade promotion would significantly influence customer satisfaction in purchasing a consumer product.This research attempted to affirm that these factors do indeed influence customer satisfaction in the context of Brand X which is a premium brand sweetened condensed milk. A personally-administered questionnaire survey was done to collect data from 80 respondents and which were then statistically analyzed using reliability, correlation and regression analysis. Findings: Results from the statistical analyses indicated that all the five examined factors are positively correlated with the satisfaction level of Brand X. Furthermore, the factors explained 63.3% of the variance in the respondents' satisfaction with Brand X.